Comparison of three methods for the sequential extraction of lignite pretreated by ionic liquid. (9th March 2022) - Ding, Ning; Li, Mei; Yue, Jinsong; Cheng, Sidan; Gao, Caiyun
Abstract: In order to improve the extraction rate of coal by solvent extraction, Lianhuatang lignite (LHT) was pretreated with 1‐butyl‐3‐methylimidazolium hexafluorophosphate ionic liquid([Bmim]PF6 ) firstly. Then, the Soxhlet extraction (SE), ultrasound‐assisted extraction (UAE), and microwave‐assisted extraction (MAE) were carried out to obtain extracts (ES1‐3, EU1‐3, and EM1‐3 ) and residues (RS1‐3, RU1‐3, and RM1‐3 ) from the Lianhuatang lignite pretreated with ionic liquid (BLHT), respectively, and CS2, acetone, and ethanol were used as solvents. The coal samples before and after the ionic liquid pretreatment were characterized by scanning electron microscope (SEM), Fourier‐transform infrared spectroscopy (FTIR), and thermogravimetric analyzer (TG). The residues were characterized by FTIR, and the extracts were characterized by a gas chromatograph/mass spectrometer (GC/MS). According to the results, ionic liquid can crack coal particles, increase the contact area of coal surface with solvent, and destroy part of the hydrogen bonds and intermolecular forces in coal, enabling easy extraction of the active small molecules. The macromolecular structure of coal is not destroyed in the three sequential extraction experiments. The types of extracts are similar under different methods, but the specific substances are very different. The total extraction rate by MAE was the highest, which was 48.70%. Microwave radiation can promote the extraction of oxygen‐containing substances, especially esters.